Ethnoveterinary practices among Gaddi pastoralists of North Western Himalayan region, Himachal Pradesh (Indian Journal of Animal Production and Management, 2024)
The present exploratory study was carried out in four districts (Kangra, Hamirpur, Bilaspur and Una) of  Himachal Pradesh, to study the ethnoveterinary practices used by Gaddi pastoralists during their low hill  migration. Thirty flocks were randomly selected from the database of AICRP on Goat Improvement and  field visits were made during October 2020- March 2021. Detailed proforma was designed to collect the  information of ethnoveterinary prctices followed by Gaddi nomads. The survey study revealed that Gaddi  nomads are till date using their traditional knowledge for treating different ailments of Sheep and Goat  in migratory conditions. Ethnoveterinary practices are more significant to the Gaddi nomads as they are  continuously migrating with their livestock throughout the year, without having prompt access to medical  facilities provided by the state Animal Husbandry department along the migratory routes. Gaddi nomads  use the ethnoveterinary practices for the treatment of various ailments viz. maggot wound, skin infection,  diarrhea, indigestion, lantana poisoning, lameness, mastitis, tympany, retention of placenta (ROP), foot  and mouth disease (FMD), respiratory problems, abortion, leech infestation, fracture, ticks & lice infestation  and wounds.
Keywords: Ethnoveterinary practices; Gaddi goat; Gaddi tribe